2010
DOI: 10.1308/147870810x12699662980871
|View full text |Cite
|
Sign up to set email alerts
|

Acute abdominal pain following fracture of a heterotopically formed bone incorporating a prolene mesh

Abstract: A case is presented of severe abdominal pain around a healed scar following fracture of a heterotopically formed bone. This should be considered an unusual differential diagnosis in patients with acute pain of unknown origin who had open abdominal surgery in the past. To our knowledge, we have also reported the first case of hetertopic bone formation incorporating a prolene mesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Beside non-genetic factors like mechanical stress, nutrition, glucose intolerance, and high body mass index, recent studies showed numerous genes are associated with the disease. Most of these genes are vital to the ossification process like NPPS, COL11A2, COL6A1, BMP2, BMP4, TGF-β1, TGF-β3 4 5 6 7 22 24 , and often aberrant expression of these genes can cause the pathological heterogeneous ossification 25 26 . This means a certain disorder in the upstream regulatory network of these critical factors may exists during the pathological process of OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…Beside non-genetic factors like mechanical stress, nutrition, glucose intolerance, and high body mass index, recent studies showed numerous genes are associated with the disease. Most of these genes are vital to the ossification process like NPPS, COL11A2, COL6A1, BMP2, BMP4, TGF-β1, TGF-β3 4 5 6 7 22 24 , and often aberrant expression of these genes can cause the pathological heterogeneous ossification 25 26 . This means a certain disorder in the upstream regulatory network of these critical factors may exists during the pathological process of OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…HMO is a rare subtype of HO occurring in the mesentery. The exact incidence and prevalence rates for HMO are unclear because many cases are believed to be asymptomatic and underdiagnosed [ 16 ]. It is believed to be relatively rare because only fewer than 100 cases have been reported so far in the English-language literature [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been only one similar case report. Nagesawaran7 reported a patient with acute abdominal pain secondary to fracture of heterotopic bone enveloping 17-year-old prolene mesh. The bone had a periosteal layer, nutrient artery and histologically confirmed lamellar bone and bone marrow.…”
Section: Discussionmentioning
confidence: 99%